Meta-Analisis : Validitas Media Booklet pada Pembelajaran Biologi (Tahun 2013-2023) - Afifah Pamela; Zulyusri Zulyusri (Institut Agama Islam Negeri Kerinci, 2024)
This study employs meta-analysis to assess the validity and utility of booklet instructional media in biology education. By analyzing data from various studies using specific keywords, 34 articles published between 2013 and 2023 were selected for evaluation. The analysis focused on content, language, presentation, and graphics. Results indicate an average validity of 90.00%, indicating high validity. Booklet media is deemed highly valid and practical, enhancing learning effectiveness and facilitating student comprehension of biology concepts. In conclusion, booklet media is a valuable resource for both educators and students in biology education.